2021
DOI: 10.1093/rheumatology/keab814
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Pyruvate Kinase M2 as a marker of vascular inflammation in giant cell arteritis

Abstract: Objectives GCA is a large vessel vasculitis in which metabolically active immune cells play an important role. GCA diagnosis is based on CRP/ESR and temporal artery biopsies (TABs), in combination with 18F-fluorodeoxyglucose ([18F]FDG)-PET/CT relying on enhanced glucose uptake by glycolytic macrophages. Here, we studied circulating Pyruvate Kinase M2 (PKM2), a glycolytic enzyme, as a possible systemic marker of vessel wall inflammation in GCA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…However, it has also been shown that inducing the tetrameric form of PKM2 via TEPP-46 suppresses pro-inflammatory responses by inhibiting IL-1ß production and inducing IL-10 [ 11 ]. In our study, we observed PKM2 expression in areas of IL-1ß+ macrophages and reported an association of PKM2 with other inflammatory and macrophage markers in both blood and tissue [ 2 ]. Therefore, we believe that TEPP-46 has potential as a therapeutic agent in GCA treatment.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…However, it has also been shown that inducing the tetrameric form of PKM2 via TEPP-46 suppresses pro-inflammatory responses by inhibiting IL-1ß production and inducing IL-10 [ 11 ]. In our study, we observed PKM2 expression in areas of IL-1ß+ macrophages and reported an association of PKM2 with other inflammatory and macrophage markers in both blood and tissue [ 2 ]. Therefore, we believe that TEPP-46 has potential as a therapeutic agent in GCA treatment.…”
mentioning
confidence: 84%
“…Firstly, as pointed out by the authors, plasma PKM2 levels are indeed elevated not only in active GCA but also in malignancies and infections [ 2 ]. Thus, elevated PKM2 levels are not specific for GCA but rather reflect glycolytic inflammatory processes.…”
mentioning
confidence: 99%
“…Additionally, our group recently demonstrated that the cellular glucose metabolism, that is, glycolytic activity, reflects systemic inflammation in patients with GCA, which may assist the diagnosis and monitoring of disease activity. 33 This may support an important link between disturbed glucose metabolism and inflammation in patients with GCA. However, the lack of association between glucose markers and inflammatory markers in patients with GCA argues against this conclusion.…”
Section: Discussionmentioning
confidence: 73%
“…Non-immune-mediated gene ontology terms associated with protein kinase A signaling, glucose and hexose transmembrane transports, cortical actin cytoskeleton organization, and mitochondrial ATP synthesis-coupled protein and glucose transports were all upregulated, while regulation associated with relaxation of cardiac muscle and cardiac muscle cell apoptotic process, hindlimb morphogenesis, inner ear receptor cell development, histone deacetylase activity, and muscle relaxation was downregulated in GCA. These may reflect the abnormalities of cellular metabolisms and cell development in GCA [ 14 , 44 , 45 ], although further investigations are needed.…”
Section: Discussionmentioning
confidence: 99%